Acceptance and management of stage fright among musicians: a manual of practical strategies - Eva Bojner Horwitz; Eva Bojner Horwitz; Eva Bojner Horwitz; Pauliina Valtasaari (Frontiers in Psychology, 2025)
It has been suggested that stage fright may be musicians’ greatest psychological stressor. This study aims to develop various mental and physical practices that form an easy-to-use “manual” for musicians with stage fright by using stick figures and concise, short, instructive texts. The recommended practices were developed based on discussions between expert researchers working with musicians’ stage fright. The manual was tested on a musician to manage unpleasant thoughts, emotions, and physical sensations caused by stage fright. Eighteen steps, rooted in self-awareness and mindfulness, gave the musician a tool to embrace stage fright as a steppingstone to greater self-expression and artistry. The manual with the 18 stick figures will be further evaluated and tested in a controlled bigger sample. The discussions revealed that by observing and accepting one’s feelings without judgment and catastrophizing, it is possible to learn to understand the needs of the body and to respond compassionately. A manual of 18 easy-to-use practical strategies could be one way to deal with stage fright.